Marine Hazard Assessment of Soluble and Nanostructured Forms of the Booster Biocide DCOIT in Tropical Waters - Perina, Fernando; Ottoni, Cristiane [UNESP]; Santos, Juliana [UNESP]; Santos, Vithória [UNESP]; Silva, Mariana [UNESP]; Campos, Bruno [UNESP]; Fontes, Mayana [UNESP]; Santana, Debora [UNESP]; Maia, Frederico; Abessa, Denis [UNESP]; Martins, Roberto (MDPI, 2023)
The encapsulation of antifouling compounds, such as DCOIT (4,5-Dichloro-2-octylisothiazol-3(2H)-one), in mesoporous silica nanocapsules (SiNC) has recently been demonstrated to be an eco-friendly alternative to decrease biocide toxicity towards marine non-target species. However, the lack of information on the chronic effects of such nanomaterials on non-target tropical species is critical for a more comprehensive environmental risk assessment. Thus, the present study aimed to assess the chronic toxicity and hazard of the soluble and encapsulated forms of DCOIT on neotropical marine species. Chronic tests were conducted with six ecologically relevant species. No effect concentration (NOEC) values were combined with NOEC values reported for tropical species to assess the hazard using the probabilistic approach to derive each predicted no effect concentration (PNEC). The SiNC-DCOIT was three- to ten-fold less toxic than soluble DCOIT. Probabilistic-based PNECs were set at 0.0001 and 0.0097 µg DCOIT L−1 for the biocide soluble and nanostructured forms, respectively. The immobilization of DCOIT into SiNC led to an 84-fold hazard decrease, confirming that the encapsulation of DCOIT into SiNC is a promising eco-friendly alternative technique, even in a chronic exposure scenario. Therefore, the present study will contribute to better management of the environmental risk of such innovative products in the tropical marine environment.
Keywords: antifouling biocides; environmental regulation; nanomaterials